(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
In this paper analysis has been done to study the humancapital status of developing economies. The multiple regression analysis technique was applied to see whetherthe effect of different factors differs significantly between thecountries. The human development indexhas been used as a proxy for judging the human capital level. Attempt has been made to find the relationshipof human development index with per capita income (PPP), gross domestic saving,health expenditure as a percent of GDP, education expenditure as a percent ofGDP, labour force as a percent of total population, share of non-agriculturesector as a percent of GDP, percentage of labour force in non-agriculturesector.